PENGARUH REMUNERASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) Studi Pada Kantor Rektorat Universitas Lambung Mangkurat Banjarmasin - Muhammad Nawawi; Ahmad Alim Bachri (Universitas Lambung Mangkurat, 2018)
The Purpose of the research to identify and analyze the effect of Remunerasi and Motivasion Work about Performance ol Civil Servants (PNS) simultaneously and partially on the Performance. The method used is quantitative research that is explanatory, with a population of 191 people, technique sampling used is stratified random sampling with a sample of 66 people who serve as respondents, data analysis tool used is multiple linear regression using SPSS software ver.16.0. The results ofthis studyconcludedthat the remunerationandmotivation to worksimultaneously and partiallypositive effect onperformance.Of the threeindepend- entvariable, the highest percentagewas97,8% remuneration(X1) compared with the twoother variables. This isbecausethatis essentiallyan employeeis unable to performanythingin general, there needs to becompensationimpetusin drivingdirectionoptimal work, compensationandjob satisfactionpolicyimplementationneed tobe included in thetraining sobeberpapositive influenceon employee performance.